"Be Current, or You Become the Old Man": Crossing the Generational Divide in Hip-Hop Education. (July 2023) - Rawls, Jason D.; Petchauer, Emery
Hip-hop culture has been an influential force on a large segment of this generation's teachers and a tool for building relationships with students. The contemporary hip-hop of today's generation differs from that of many hip-hop educators/pedagogues. This case study explored how one hip-hop generation teacher attempted to cross this generational divide rather than discount youth culture in the classroom. The findings of this study focus on how the teacher's personal identification with hip-hop culture informed his relationships with students and how he drew from key narratives and ideas in hip-hop to communicate his views of his classroom community.